2016
DOI: 10.3389/fpls.2016.00329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Farming in Artemisia annua, a Promising Approach to Improve Anti-malarial Drug Production

Abstract: Malaria is a parasite infection affecting millions of people worldwide. Even though progress has been made in prevention and treatment of the disease; an estimated 214 million cases of malaria occurred in 2015, resulting in 438,000 estimated deaths; most of them occurring in Africa among children under the age of five. This article aims to review the epidemiology, future risk factors and current treatments of malaria, with particular focus on the promising potential of molecular farming that uses metabolic eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 176 publications
(231 reference statements)
0
31
0
Order By: Relevance
“…The results showed that AaWRKY1 increased the artemisinin content through ADS and CYP regulation (27). As far as AN molecule in Artemisia is in low concentration, it is quite expensive, and different genetic manipulation approaches are difficult to do; thus, regulation of AN genetic pathway and other biological processes is costly (28). Artemisinin and total flavonoids levels were higher in samples obtained from high land areas (western and south western region) compared to those obtained from lowland regions.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that AaWRKY1 increased the artemisinin content through ADS and CYP regulation (27). As far as AN molecule in Artemisia is in low concentration, it is quite expensive, and different genetic manipulation approaches are difficult to do; thus, regulation of AN genetic pathway and other biological processes is costly (28). Artemisinin and total flavonoids levels were higher in samples obtained from high land areas (western and south western region) compared to those obtained from lowland regions.…”
Section: Resultsmentioning
confidence: 99%
“…Artesunate (ARS) is a semi‐synthetic derivative of artemisinin, a sesquiterpene lactone compound that is naturally produced by Artemisia annua L. (Pulice, Pelaz, & Matías‐hernández, ; Zuo, Li, Liu, Feng, & Chen, ). Over the past several years, ARS has been used as an outstanding antimalarial drug, and an increasing number of further pharmacological actions have been reported (Noubiap, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the economic importance of artemisinin, the sole dependency on plant-based production periodically fails to meet the global demand due to irregular agricultural supply, which then renders fluctuations in the market and reductions in artemisinin inventory [9, 10]. To mitigate supply uncertainties and price volatility, biotechnological alternatives such as genetic modification, crop breeding and semi-synthetic production were considered with the latter far more successful [11]. The semi-synthesis approach has the production capacity to yield approximately 60 tonnes of artemisinin annually, but it also involves the trade-off between efficiency and profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, artemisinin biosynthesis occurs in glandular secretory trichomes that are present on foliage, stems and inflorescences of the A. annua plant [15, 16]. Due to its compartmentalized synthesis and influence by physiological, seasonal and environmental factors, artemisinin concentration is highly variable with reported values of 0.1 – 10 mg g -1 dry weight (DW) [11, 17]. With the biosynthetic pathway of artemisinin formation fully elucidated over the past decade, it was learnt that within the species A. annua two contrasting chemotypes can be distinguished, which are characterized by the differing contents of artemisinin and its precursor (Fig 1).…”
Section: Introductionmentioning
confidence: 99%